Evaluation of residual palmer amaranth control with herbicides coated on fertilizer - Linn, Summer L.; Norsworthy, Jason K.; Barber, Tom; Thrash, Benjamin; Roberts, Trenton (Frontiers in Agronomy, 2024)
Herbicide-coated fertilizers have the potential to provide lasting control of problematic weeds while simultaneously reducing the risk of injury to cotton, thus reducing yield penalties. Therefore, research was conducted in Fayetteville and Marianna, AR, to evaluate which herbicides coated on fertilizer provide lasting control of Palmer amaranth without increased risk of cotton injury. Eight herbicides were coated onto a blend of 196 kg ha-1 of urea and 112 kg ha-1 of muriate of potash and applied at the 6- to 8-leaf growth stage over the top of cotton. In Marianna, florpyrauxifen-benzyl provided the lowest control, which was 73% averaged over 14 and 28 d after treatment (DAT). The level of control provided by florpyrauxifen-benzyl did not differ from the other treatments in Fayetteville. While some herbicide treatments did have decreased control by 28 DAT, they were still effective, providing no less than 93% control. Palmer amaranth density differed among herbicides only in Marianna, where florpyrauxifen-benzyl-treated plots had a higher weed density. None of the herbicide treatments in either of the experiments caused any adverse effects on the crop as measured by visual injury, seedcotton yield, and crop groundcover. Most of the coated fertilizer treatments provided high levels of Palmer amaranth control and demonstrated the weed management potential of this herbicide application method. These results highlight the potential of implementing herbicides that are not labeled for over-the-top postemergence applications in cotton as coated fertilizers, as this method reduces the risk of injury and yield penalties.